Medically active ingredient in Tarragon (Artemisia dracunculus L.) affected by adding fish emulsion and Vermicompost - Najwan Abdulameer Abd Aljashami; Kadum Mohammed Abdullah (Journal of Kerbala for Agricultural Sciences, 2024)
The experiment was carried out in the canopy of the Department of Horticulture and Landscape - Faculty of Agriculture - Kerbala University during the spring semester 2023. The study was carried out as a factor experiment by designing complete random block design(R.C.B.D) with three repetitions. The experiment included two factors, the first was a fish emulsion and was added in four concentrations, namely 0, 1, 2, 3%, and the second factor was the addition of Vermicompost with four levels 0, 25, 50, 100 g Pot-1, the averages were compared using the lowest significant difference at the probability level of 0.05. The results showed that the addition of fish emulsion significantly affected each type of flavonoid glucosides (Vitexin, Luteolin-3-galctasides, Rutin, Eriodityol, Quercetin-3-rhamnoside), where the concentration (3%) treatment gave the highest rate, reaching (1119.73، 914.28، 1013.6، 1193.81، 1308.91) on the relay . The addition of Vermicompost affected the types of glucosides (Vitexin, Luteolin-3-galctasides, routine, Eriodityol), the concentration (g pot-1) gave the highest rate, reaching (1056.22, 962.07, 1008.0, 1055.79) sequentially The interaction between the two study factors showed a significant effect on glucosides (Vitexin, Luteolin-3-galctasides, Rutin, Eriodityol, Quercetin-3-rhamnoside), where the (3%, and 100 g Pot-1) interference treatment gave the highest rate (1448.60، 1464.72، 1423.3، 1463.82،1441.84 ) on the relay. It can be concluded from this study that fertilizers resulting from organic waste can be used as sources of fertilization for plants to reduce the use of chemical fertilizers to reduce environmental damage and follow the system of sustainable agriculture.